THE USE OF IMATATION TECHNIQUE TO IMPROVE THE STUDENTS` SPEAKING ABILITY AT THE SECOND GRADE STUDENTS OF TSANAWIYAH NURUL YAQIEN SAYANG-SAYANG - Tawali (Sinar Lima, 2025)
This study aimed to describe that the use of the Imitation Technique to improve the students` speaking ability. This study was classroom action research (CAR) or mix-method to design in order to answer statement of the problem. There was only one research question in this study. How does the use of the Imitation Technique to improve student` speaking ability at the second-grade student of Tsanawiyah in academic year 2025/2026? The subject of the study were 26 students. The technique of collecting data were pre-test and post-test, which was in the form of describing tourism object at the pre-test and post-test was describing popular artist to obtain the data. The pre-test score was This was conducted one cycle because the cycle could be achieved the criterion of success or KKM in that school was 75, and the pre-test was scored 1823: 26= 70,2, and the post-test was scored 2212,2: 26= 8,1. It could be conclude based on the result of post-test in the first cycle after treating by using The Imitation Technique to the student at Tsaniwiyah there were increased the number of score from 70,2 up to 80,1, therefore the imitation technique was used in teaching speaking was significance could be seen from the post-test result bigger than the result of pre-test in this study. It meant that the success of the imitation technique in improving the student` speaking ability.